VITAMINS A, D, E AND K IN CALVES AND THEIR EFFECTS ON THE BODY - Associate Professor: N. Farmonov; Senior Teacher: J. E. Rejepbayev; Student: S. K. Tajimova (Web of Journals Publishing, 2025)
This article discusses the most common vitamin deficiencies in calves and their impact on health. Vitamins play a crucial role in maintaining calf health. Deficiencies in vitamins A, D, E, and K can cause growth and development problems in calves. The article also includes helpful tips on what to do to prevent these vitamin deficiencies.
Keywords: Calf, vitamin deficiency, vitamins A, D, E, K, health, effects of nutrients.